2015
DOI: 10.1167/15.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of interference effect by low spatial frequency information priming in an emotional Stroop task

Abstract: The affective prediction hypothesis assumes that visual expectation allows fast and accurate processing of emotional stimuli. The prediction corresponds to what an object is likely to be. It therefore facilitates its identification by setting aside what the object is unlikely to be. It has then been suggested that prediction might be inevitably associated with the inhibition of irrelevant possibilities concerning the object to identify. Several studies highlighted that the facilitation of emotional perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
2
13
2
Order By: Relevance
“…(2006), LSF information would be projected directly to the orbitofrontal cortex, generating early activity (at 130 ms), then guiding recognition in the temporal areas (at 180 ms) in the fusiform gyrus (Bar et al ., 2006), brain regions in which activity is often found to be atypical in ASD (Critchley et al ., 2000; Kovarski et al ., 2019). These projections would be at the origin of predictions and thereby guide perceptual processes, allowing the recognition of stimuli (Beffara et al ., 2015). Several authors have suggested predictive coding abnormalities in persons with ASD as they could appear less influenced by contextual information and/or past experience (Pellicano & Burr, 2012; Sinha et al ., 2014) as their perception is less distorted and often reported as enhanced (Mottron et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(2006), LSF information would be projected directly to the orbitofrontal cortex, generating early activity (at 130 ms), then guiding recognition in the temporal areas (at 180 ms) in the fusiform gyrus (Bar et al ., 2006), brain regions in which activity is often found to be atypical in ASD (Critchley et al ., 2000; Kovarski et al ., 2019). These projections would be at the origin of predictions and thereby guide perceptual processes, allowing the recognition of stimuli (Beffara et al ., 2015). Several authors have suggested predictive coding abnormalities in persons with ASD as they could appear less influenced by contextual information and/or past experience (Pellicano & Burr, 2012; Sinha et al ., 2014) as their perception is less distorted and often reported as enhanced (Mottron et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Racial biases have been robustly reported in face detection but the effects may depend on context, culture and task [5]. The dependency of racial bias upon these factors is not surprising given that high-level conceptual or social information are known to modulate low-level mechanisms of visual perception [6,7,8]. Affective valence modulates object identification during visual perception [9]but personality traits, ideologies, motivation, and social context also play a large part in face processing and categorization [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, our results describe a close interaction between bottom-up and top-down processes with which both visual uncertainty and expectations drive the accumulation of evidence during visual search. On a behavioral level, this is an extension of existing models of top-down recognition that suggest fast and automatic interactions between bottom-up and top-down visual streams (Bar, 2004;Beffara et al, 2015;Kauffmann, Chauvin, Guyader, & Peyrin, 2015). This raises important questions about bottom-up and topdown integration within and across fixations during scene exploration.…”
Section: Resultsmentioning
confidence: 57%